Ekranisasi Novel My Nerd Girl karya Aidah Harisah ke Web Series - Ayu Anni Safitri; Muhammad Adek (Persona: Kajian Bahasa dan Sastra, 2023)
The aims of this study were: (1) to describe the shrinking of the character, plot, and setting elements in Aidah Harisah's novel My Nerd Girl's expansion into the My Nerd Girl web series directed by Agus Nugroho, (2) to describe the addition of character, plot, and background elements in ecranization of the novel My Nerd Girl to the Web series My Nerd Girl directed by Agus Nugroho, (3) describes the changes in variations in characters, plots, and settings in the Web series My Nerd Girl directed by Agus Nugroho based on the story text of the novel My Nerd Girl by Aidah Harisah. The object of this research is the novel My Nerd Girl by Aidah Harisah which was published in 2019 and the Web Series My Nerd Girl by director Agus Nugroho in 2022. The method used in this research is literary research with a descriptive method. The form of this research data is in the form of the entire contents of the text in the novel and dialogue as well as audiovisual elements in the Web Series which are related to aspects in the ecranization process. The technique of collecting data for this research is non-involved observation and note-taking techniques. Data analysis techniques are content analysis techniques and analytical comparisons. The results of this study found all aspects of ecranization including shrinking, adding, and changing variations. The implementation of these three aspects is manifested in the elements of characterization, plot and setting. The genre shift from romantic to mystery is the main motive in the process of ecranization in these two works.